Commercialization secrets for scientists and engineers - Szycher, M. (Michael) (Boca Raton : CRC Press, 2017)
Commercializing a knowledge-based product or service requires a realistic, methodical approach combined with a great deal of perseverance. Commercialization Secrets for Scientists and Engineers serves as a high-level guide to answering key questions and critical issues that confront founding entrepreneurs on their quest to commercialize their knowledge-based innovations. It highlights the unique problems shared by all technologists across knowledge-intensive fields and how to overcome the most predictable obstacles faced by technology entrepreneurs. It demystifies the process of commercializing advanced products that require a high degree of specialized knowledge. Typically, these are disruptive technologies with the potential to revolutionize whole industries. The book simplifies the launch of high-tech ventures such as pharmaceuticals, genetic and biotechnology products, wireless devices, fuel cells, and minimally invasive medical devices. Additionally, it will help readers bring their disruptive technologies to profitability. Offers key descriptions of the commercialization process from idea to profitability Discusses business development on a budget Covers initial decisions, such as whether to form a partnership or proprietorship, market focus, pricing, funding, and the like Describes issues related to product launch Uncovers pathways to becoming profitable--
section 1. Development on a shoestring -- section 2. Classical initial decisions -- section 3. Product launch -- section 4. Pathways to profitability.
Keywords: Technology transfer; Research, Industrial; New business enterprises; Science -- Vocational guidance; Engineering -- Vocational guidance